Temporal trends and geographical disparities in comprehensive stroke centre capabilities in Japan from 2010 to 2018. Issue 8 (6th August 2020) - Kurogi, Ai; Nishimura, Ataru; Nishimura, Kunihiro; Kada, Akiko; Onozuka, Daisuke; Hagihara, Akihito; Ogasawara, Kuniaki; Shiokawa, Yoshiaki; Kitazono, Takanari; Arimura, Koichi; Iihara, Koji
Abstract : Objectives: Comprehensive stroke centre (CSC) capabilities are associated with reduced in-hospital mortality due to acute stroke. However, it remains unclear whether there are improving trends in the CSC capabilities or how hospital-related factors determine quality improvement. This study examined whether CSC capabilities changed in Japan between 2010 and 2018 and and whether any changes were influenced by hospital characteristics. Design: A hospital-based cross-sectional study. Setting: We sent out questionnaires to the training institutions of the Japan Neurosurgical Society and Japan Stroke Society in 2010, 2014 and 2018. Participants: 749 hospitals in 2010, 532 hospitals in 2014 and 786 hospitals in 2018 participated in the J-ASPECT study, a nationwide survey of acute stroke care capacity for proper designation of a comprehensive stroke centre in Japan. Main outcome measures: CSC capabilities were assessed using the validated scoring system (CSC score: 1–25 points) in 2010, 2014 and 2018 survey. The effect of hospital characteristics was examined using multiple logistic regression analysis. Results: Among the 323 hospitals that responded to all surveys, the implementation of 13 recommended items increased. The CSC score (median and IQR) was 16 (13–19), 18 (14–20) and 19 (15–21) for 2010, 2014 and 2018, respectively (p<0.001). There was a ≥20% increase in six items (eg, endovascular physicians, stroke unit and interventional coverage 24/7), and a ≤20% decrease in community education. A lower baseline CSC score (OR: 0.82, 95% CI 0.75 to 0.9), the number of beds≥500 (OR: 3.9, 95% CI 1.2 to 13.0) and the number of stroke physicians (7–9) (OR: 2.6, 95% CI 1.1 to 6.3) were associated with improved CSC capabilities, independent of geographical location. Conclusions: There was a significant improvement in CSC capabilities between 2010 and 2018, which was mainly related to the availability of endovascular treatment and multidisciplinary care. Our findings may be useful to determine which hospitals should be targeted to improve CSC capabilities in a defined area.